The Effect of Promotion Through Food Vlogger on Tiktok Social Media on Buying Interest in Dobro Coffee Culinary Businesses - Nur Aulia, Almaura; Kusumaningrum, Anisa Putri (Jurnal Manajemen Pelayanan Hotel, 2022)
The purpose of this study is to measure how much customer interest in Dobro Coffee culinary business is from promotion through Food Vlogger on Tiktok Social Media. The type of research used in this research is quantitative research with survey method. The number of samples was taken using the Slovin formula and the results obtained a minimum sample size of 100 people using non-probability sampling with purposive sampling as a sampling technique. The data collection technique in the study was carried out by distributing it to respondents via google form. The data obtained was then analyzed by statistical tools assisted by the SPSS program using Validity Test, Reliability Test, and multiple linear regression analysis. The results of the study found that Promotion Through Food Vlogger had an influence on Buying Interest in the Dobro Coffee Culinary business; Promotion through Tiktok has an influence on Buying Interest in the Dobro Coffee Culinary business; Promotion through Food Vlogger with Tiktok has an influence on Buying Interest in the Dobro Coffee Culinary business. Keywords : Promotion, Food Vlogger, Social Media, TikTok, Buying Interest